The perception of the African-American community through the eyes of the Hispanic media in the U.S.: a critical discourse analysis of the reporting of the death of Michael Brown - De Cort, Stephenie; De Schutter, An; Vangehuchten, Lieve (Círculo de Lingüística Aplicada a la Comunicación, 2016)
In this paper, 36 English and 38 Spanish news articles were selected from English and Spanish newspapers and magazines published in the U.S.A. from August 2014 to November 2014. All articles discuss the death of Michael Brown, the ensuing protests and police investigations. A discourse analysis shows that there are few differences between reporting by the mainstream and the Hispanic media. Like the mainstream media, the Hispanic media adopts a neutral point of view with regard to the African-American minority. However, it presents a negative opinion with regard to the police. It appears that the Hispanic media does not explicitly side with the African-American community, but rather agrees more with the mainstream media’s opinion and is substantially influenced by it.